Lateralised semantic and indirect semantic priming effects in people with schizophrenia - Weisbrod, Matthias; Maier, Sabine; Harig, Sabine; Himmelsbach, Ulrike; Spitzer, Manfred (The British journal of psychiatry, 1998)
Background - In schizophrenia, disturbances in the development of physiological hemisphere asymmetry are assumed to play a pathogenetic role. The most striking difference between hemispheres is in language processing. The left hemisphere is superior in the use of syntactic or semantic information, whereas the right hemisphere uses contextual information more effectively. - - - Method - Using psycholinguistic experimental techniques, semantic associations were examined in 38 control subjects, 24 non-thought-disordered and 16 thought-disordered people with schizophrenia, for both hemispheres separately. - - - Results - Direct semantic priming did not differ between the hemispheres in any of the groups. Only thought-disordered people showed significant indirect semantic priming in the left hemisphere. - - - Conclusions - The results support: (a) a prominent role of the right hemisphere for remote associations; (b) enhanced spreading of semantic associations in thought-disordered subjects; and (c) disorganisation of the functional asymmetry of semantic processing in thought-disordered subjects.
Elektronische Reproduktion der Druck-Ausgabe: 02 January 2018
Gesehen am 23.12.2021